Growth Performance of Eucheuma Cotonii by Immersing in Several Macroalgae Extract - Cokrowati, Nunik; Setyowati, Dewi Nur’Aeni; Kurnianingsih, Rina (Aquacultura Indonesiana, 2017)
Macro algae in West Nusa Tenggara are potential in types and quantities. One of the types that have only been economically used is seaweed, such as Eucheuma cottonii, Eucheuma spinosum, Eucheuma striatum and Gracillaria sp. In general, all macro algae can be used for various purposes such as pharmacy, agriculture, livestock, and food ingredient. Macro algae commonly have the growth hormones and contain primary and secondary metabolites. The growth hormones in macro algae are called cytokinin, auxin and absicic acids. The objective of this study was to determine the effect of macro algae extracts to the growth of Eucheuma cottonii. This study was carried out in Ekas Bay, Ekas Buana Village, Jerowaru District, of East Lombok, West Nusa Tenggara, between May to September 2016. Eucheuma cottonii was cultivated on the 8 m X 8 m size of longline and 40 ris of load. Spacing between ris was 1 m and distance between clumps was 25 cm. Cultivation was carried out by using Eucheuma cottonii seed with average weight of 100 g and weighing was carried out every 7 days. Macro algae used as extract included Sargassum aquifolium, Ulva sp. and Turbinaria sp. Extracts were put into immersion at 5% concentration. The parameters measured were the absolute growth and Specific Growth Rate of Eucheuma cottonii, and the water quality. The results showed that the addition of macro alga extracts significantly affected the growth of Eucheuma cottonii.